Deep Learning Utilized for Person Recognition Based on the Biometric Features of the Periocular Region - Nascimeno, Leonardo Ferreira; Souza, Jones Mendonça de (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2022: Anais Estendidos da XXXV Conference on Graphics, Patterns and Images, 2022)
This article proposes the use of deep learning technologies to perform visual biometric recognition. The results obtained by convolutional neural networks trained to perform multi-class classification based on the visual features of the human periocular region are presented and discussed, in addition to being compared with results obtained using pattern recognition for biometric recognition from human iris textures.